2019
DOI: 10.1101/681999
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromatin accessibility dynamics ofChlamydia-infected epithelial cells

Abstract: Chlamydia are Gram-negative, obligate intracellular bacterial pathogens responsible for a broad spectrum of human and animal diseases. In humans, Chlamydia trachomatis is the most prevalent bacterial sexually transmitted infection worldwide and is the causative agent of trachoma (infectious blindness) in disadvantaged populations. Over the course of its developmental cycle, Chlamydia extensively remodels its intracellular niche and parasitises the host cell for nutrients, with substantial resulting changes to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 87 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…As a result, many infection and disease processes at the cellular and tissue level remain largely unknown or poorly characterized in vivo . Gene expression profiling of Chlamydia -infected cells by microarray (Porcella et al, 2015), dual RNA-Seq (Humphrys et al, 2013; Marsh et al, 2018), or other genome-scale analyses (Hayward et al, 2019) are powerful techniques to help deconvolute these interactions and processes. However, these and similar genome-scale analyses of infected cells have typically been performed on bulk cell populations, i.e., infected cell monolayers in vitro , or selectively sorted/purified subsets of cell populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, many infection and disease processes at the cellular and tissue level remain largely unknown or poorly characterized in vivo . Gene expression profiling of Chlamydia -infected cells by microarray (Porcella et al, 2015), dual RNA-Seq (Humphrys et al, 2013; Marsh et al, 2018), or other genome-scale analyses (Hayward et al, 2019) are powerful techniques to help deconvolute these interactions and processes. However, these and similar genome-scale analyses of infected cells have typically been performed on bulk cell populations, i.e., infected cell monolayers in vitro , or selectively sorted/purified subsets of cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…Clustering, pseudotime and cell state prediction analyses demonstrated that Chlamydia -treated cells at 3 h are readily distinguishable from Chlamydia -treated and mock-infected cells at 6 and 12 h. Curiously, cells at 6 and 12 h clustered together and could not be further deconvoluted from each other, possibly showing that host cell transcription at these times is broadly similar. A recent FAIRE-Seq analysis of Chlamydia -infected epithelial cells, examining patterns of host cell chromatin accessibility over the developmental cycle (Hayward et al, 2019), found that 12 h post-infection was relatively quiescent in terms of host cell transcriptional activity. This finding is reflected by our scRNA-Seq analyses here and may be extended to 6 h post-infection.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, cells at 6 and 12 hours clustered together and could not be further deconvoluted from each other, showing that host cell transcription at these times is broadly similar. A recent FAIRE-Seq analysis of Chlamydia-infected epithelial cells, examining patterns of host cell chromatin accessibility over the developmental cycle[54], found that 12 hours post infection was relatively quiescent in terms of host cell transcriptional activity. This finding is reflected by our scRNA-Seq analyses here and may be extended to 6 hours post-infection.…”
mentioning
confidence: 99%